The Rhetoric of Solidarity: Nature and Measurement of Social Cohesion in the Self-representation of Civil Society Organizations - Rico Neumann; Barbara Pfetsch; Swen Hutter; Simon Koschut; David Schieferdecker; Jule Specht (Social Indicators Research, 2023)
Scholars have called to study how social cohesion is discursively negotiated and produced in communication behavior. However, empirical evidence remains scarce. In this study, we investigate to what extent and how civil society organizations (CSOs), part of the backbone of social integration in modern democracies, make references to social cohesion in their public self-portrayals. We develop a standardized measure for content analyzing the manifestation of social cohesion along three theoretical dimensions: social relations, connectedness, and orientation towards the common good. We apply our innovative content measure to the external communication of an original sample of nearly 800 CSOs in Germany, using their websites. Subsequently, we use data from an accompanying organizational survey of these institutions to investigate whether and how certain organizational features help explain variance in social cohesion rhetoric. Findings suggest that CSOs' external communications employ themes from all key dimensions of social cohesion, revealing a fair amount of variation on all three subdimensions and a summary index of the overall strength social cohesion rhetoric. These different emphases are contingent upon various organizational characteristics, namely the spheres in which CSOs are primarily active, their locations, and their target groups. Whereas culturally and media-oriented organizations as well as sports clubs are largely reluctant to make references to social cohesion, politically active CSOs and those addressing socially disadvantaged communities tend to push more in this direction. The latter tend to operate in more professionalized structures, indicating that referencing social cohesion legitimizes these groups' political and social purposes in the public sphere.
Keywords: 300; Social cohesion; Solidarity; Civil society organizations (CSOs); Public discourse; Content analysis; Organizational survey